indonesia Pemanfaat Adobe Photoshop dalam Dunia Design di Sekolah SMK UISU - Heru Satria Tambunan Tambunan; Indra Gunawan; Sumarno Sumarno (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
For some people, learning ICT has become a skill that is commonly used every day to build their business, but for beginners who are just starting out, there are many challenges to be overcome and unanswered questions. In short, explaining and providing training on Utilization in the use of ICT for UISU Vocational School Students in Simalungun Regency which is directed to students to learn the use of ICT. The use of adobe photoshop is where it can help students be able to develop to increase their business in graphic design